Letter: Determination of Ionization Energies of a Monoterpene Series by Atmospheric Pressure Photoionization Using Tunable Vacuum Ultraviolet Synchrotron Radiation. Issue 5 (October 2014) - Méjean, Marie; Giuliani, Alexandre; Brunelle, Alain; Touboul, David
Monoterpenes are the main class of biogenic volatile organic compounds. They promptly react with oxygen and nitrogen species, leading to the formation of secondary aerosols. The determination of their physicochemical properties, such as their ionization energies (IEs), is crucial to understand better their reactivity. We previously introduced a modified atmospheric pressure photoionization source coupled to a tunable vacuum ultraviolet source at the SOLEIL synchrotron radiation facility. Here, this set-up is employed to determine IEs of ten monoterpenes with a good precision (±50 meV) and a small sample consumption limited to 10 μg.